Uric Acid Contributes to Obesity-Paradox of the Outcome of Ischemic Stroke - Tang, Hefei; Mo, Jinglin; Chen, Zimo; Xu, Jie; Wang, Anxin; Dai, Liye; Cheng, Aichun; Wang, Yongjun (Frontiers in Neurology, 2019)
Background: The mechanism of obesity paradox in stroke is not clear. This study aimed to investigate whether uric acid (UA) contributes to obesity-stroke outcome paradox. Material and Methods: The study cohort consisted of 1,984 IS patients recruited in the ACROSS-China study. Serum UA and BMI were measured at admission. Low and high BMI groups were defined by the threshold of 24, and low and high UA by the age- and sex-specific median. Poor outcomes were defined as modified Rankin scale score ≥3 in one year after onset. Results: UA was significantly and positively correlated with BMI. Lower levels of UA and BMI were significantly associated with higher risk of poor outcomes. Incidence of the poor outcome was 34.5%, 29.4%, 27.7% and 23.5% in the BMI/UA groups of low/low, high/low, low/high and high/high, respectively, with p=0.001 for trend. The association between low UA and poor outcome was significant in lower BMI groups (odds ratio=1.36, p=0.006 in quartile 1 and 1.28, p=0.021 in quartile 2), but the odds ratios were not significant in the BMI quartile 3 and 4 groups, with p=0.038 for trend. The adverse effect of lower UA was significant in males, but not in females, with p=0.006 for sex difference. Conclusions: These findings suggest that low UA and low BMI have a joint effect on poor outcomes in IS patients. Across BMI categories, uric acid is differentially associated with functional outcome after stroke. This effect of low UA in the low BMI groups may be one of the mechanisms underlying the obesity-stroke paradox of the outcome in IS patients.